An antibacterial porous calcium phosphate bilayer functional coatings on titanium dental implants. Issue 2 (15th January 2023) - Kei Lung, Christie Ying; Khan, Abdul Samad; Zeeshan, Rabia; Akhtar, Sultan; Chaudhry, Aqif Anwar; Matinlinna, Jukka Pekka
Abstract: Background: The design of biological active and antibacterial implant coating remains a challenging topic to ensure early implant fixation and to prevent peri-implantitis. In this laboratory work, we reported a newly designed antibacterial porous calcium phosphate (CP) bilayer functional coating on titanium implant incorporated with molybdenum trioxide. Methods: The coating was prepared by using a sol-gel template process. The physicochemical and biological properties of the coatings were investigated by Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), in vitro coating degradation, in vitro mineral calcium phosphate formation, cell proliferation and antibacterial tests. Results: the porous calcium phosphate bilayer coating enhanced the mineral calcium phosphate formation compared with calcium phosphate coating. Cell proliferation test using MC3T3-E1 osteoblasts showed that the porous calcium phosphate bilayer coating promoted cell growth. Antibacterial test against S. aureus showed that the porous calcium phosphate bilayer coating incorporated with molybdenum oxide exhibited a better antibacterial activity than calcium phosphate coating Conclusions: a combination of porous structure, bilayer coating and doped molybdenum oxide is crucial to improve the performance of calcium phosphate coating.